Measurement of the production of high-pT electrons from heavy-flavour hadron decays in Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; Ohlson, Alice; et al. (Physics letters, 2017)
Electrons from heavy-flavour hadron decays (charm and beauty) were measured with the ALICE detector in Pb-Pb collisions at a centre-of-mass of energy sNN=2.76 TeV. The transverse momentum (pT) differential production yields at mid-rapidity were used to calculate the nuclear modification factor RAA in the interval 3<pT<18 GeV/c. The RAA shows a strong suppression compared to binary scaling of pp collisions at the same energy (up to a factor of 4) in the 10% most central Pb-Pb collisions. There is a centrality trend of suppression, and a weaker suppression (down to a factor of 2) in semi-peripheral (50-80%) collisions is observed. The suppression of electrons in this broad pT interval indicates that both charm and beauty quarks lose energy when they traverse the hot medium formed in Pb-Pb collisions at LHC.
Im Titel ist T tiefgestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Alice Collaboration: J. Adam, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, L. Leardini, J. Mercado Pérez, H. Oeschler, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M. Schmidt, J. Stachel, D.F. Weiser, B. Windelband, A. Zimmermann [und weitere]
Gesehen am 19.06.2019